Cultural Variables Affecting the Roles of the Tribal Society A Socio-Anthropological Research in the Khalidiya District Center in Anbar Governorate - SHARQI, MUAYAD MNFI MOHAMMED (Al-Adab Journal, 2015)
The effective cultural variables in the roles of th tribal variable society in Khalidiya area , and changing roles in tribal rural community in Iraq roles, changing the Iraqi rural women , and the changing roles of women in the rural tribal community in Anbar province.Research depends on preliminary data, as the researcher prepared a questionnaire of a random sample stratified pf 24 items have been distributed on 300 people in Khalidiya area , as was the use of the descriptive approach to achieve the aimss identified on the phenomenon of intolerance tribal family in a society Khalidiya and its impact on their attitudes towards participation in the community development , and the disclosure of the impact of cultural variables in the tribal society of family ( sex- agen- residence " rural - urban " - Education ) on intolerance , , As well as detect the phenomenon of the current status of women in the family to what gain from cultural dimensions and effects on social life in general , and the disclosure of the current situation of women in the family and the most important factors that hampered from doing their roles within the family and society and stand on the commitment of generations to uphold the various customs and traditions patriarchy anti-woman .Research results showed the impact of cultural change on the construction and functions of the family in the following:- The extended family is still continuing with the growing emergence of the nuclear family .- The independence of the nuclear family , but they have not abolished the adult role in the family , as you return to them in the fundamental matters .- The participation of the wife in the decision-making process with a change in their roles within the home- The high literacy rate , especially among females with the traditional view has changed .The study found some of the recommendations , including:- Further studies in rural communities about social and traditional values ​​and the wrong habits in the countryside